(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The present study aimed to conduct an exploration of the literature in order to define trends on the research topic "Virtual education and personal relationships worldwide”. The search of the available literature was carried out using the Scopus index database, considering all types of documents published from the years 1997 to 2022. As a result, 520 research papers were obtained, which were downloaded from Scopus in csv file format, which was processed with the Biblishiny application of the statistical software Rstudio, from which all the metrics used in this work were extracted. The findings found were the following: Scientific articles were the most predominant in the search carried out (410), annual productivity showed an increasing trend from the years 2017 to 2022, being the latter the most productive with 178 published research papers and finally the journal, country and authors that have the most impact in the field of study are Frontiers in psychology, China, and Wang Y.